EFEKTIVITAS DAN EFISIENSI PENERIMAAN DAERAH DISTRIK DILI - Araujo, Miguel de; Wiagustini, Ni Luh Putu; Purbawangsa, Ida Bagus Anom (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.12.TAHUN 2018DO - 10.24843/EEB.2018.v07.i12.p04, 2018)
This research was conductedat the Department ofTaxation of DiliBased on the analysis,the rate of growth of revenue receipts Dili districts experiencing growth fluctuating.Level RentalTaxrevenue receipts effectiveness Dili district experienced a fluctuating level, at this level as very effective.Level efficiency of the revenue receipts of the results of the analysis This suggeststhat local governments have been able to work very well because it has been able to meet the targets seteven exceeding the targetit self,this suggests that the government's performance has been very good.